Regulation of cardiac protein quality control by deubiquitinating enzymes - Poetsch, Mareike Susann; Justus Liebig University Giessen (My University, 2018)
Sustained protein homeostasis proteostasis is particularly important in the heart as cardiomyocytes are limited to self-renewal. The interaction between molecular chaperones and protein catabolic pathways, above all, the ubiquitin proteasome system (UPS) and (selective) autophagy, plays a critical role for protein turnover in the heart. Malfunctions of these processes due to increased stress caused by gene mutations, translational errors, or reduced efficiency result in accumulation of toxic protein aggregates and the progression of several cardiac diseases, such as dilated cardiomyopathy (DCM). This study identified the ubiquitin-specific peptidase USP5 as a cell-type specific, critical deubiquitinating enzyme for polyubiquitin turnover and proteostasis in mice and human cardiomyocytes. Loss of USP5 in cardiomyocytes caused effects ranging from profound accumulation of polyubiquitin chains, defective polyubiquitin turnover, and strong suppression of proteolytic activity of the proteasome, irreversibly resulting in the formation of ubiquitin-conjugated protein aggregates. Impaired clearance of such aggregates by selective autophagy augmented the cytotoxic cellular stress response, progressively resulting in cardiac remodeling, severe DCM, and sudden death. Similar to the DCM phenotype observed in the USP5 mouse model, cardiomyocytes from human individuals with end-stage DCM displayed substantially reduced USP5 protein levels and accumulation of ubiquitinated protein aggregates lacking USP5. Interestingly, overexpression of USP5 in cardiomyocytes expressing a mutant form of titin, known to cause cardiomyopathy, abrogated formation of titin aggregates through elevated proteasomal activity. These findings might pave the way for a new innovative therapeutic strategy by which USP5 may aid in reversing disease-related protein aggregation caused by truncated or missense mutations in structural genes. In summary, the findings of this study provide the first genetic evidence for the crucial role of USP5 in the regulation of UPS-dependent proteolysis and selective autophagy, two processes that are instrumental for protein quality control in the heart.
Keywords: proteostasis; protein quality control (PQC); deubiquitinating enzymes (DUBs); ubiquitin; UPS; ddc:570